English Education Development Effort With A Communicative Language Teaching (CLT) Approach Method - Ilham Ramadhan; Lintang Shaban Nanda; Putri Risma Alfiona; Wardah Syaima' Nejed (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The implementation of foreign language learning in Indonesia is an effort to develop the education of the Indonesian nation to be able to absorb and follow the development of science and technology in the world, as well as a way to enter the global society. The use of English as a foreign language in Indonesian education aims to improve the quality of students so that they can compete in the international realm. In learning English, speaking ability is a very important aspect, especially for teachers. Implementation in the classroom, the teacher is expected to be a good facilitator and motivator so that students have an increasing enthusiasm for learning. One of the teaching methods that can be applied is Communicative Language Teaching (CLT). The development of English education can be done using the Communicative Learning Teaching (CLT) method where the concept used is through Communicative Competence. The method of writing this article uses qualitative research methods with a literature review approach. The result of this research is the author's presentation of the developmental efforts that can be made by teachers and students in developing English education.